THE EFFECT OF BLENDED LEARNING QUALITY AND SELF-DIRECTED LEARNING ON ECONOMIC STUDY’S LEARNING OUTCOMES OF SENIOR HIGH SCHOOL IN BOGOR CITY - Darmah, Novina; Saptono, Ari; Wibowo, Agus (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
The purpose of this study was to determine the direct and indirect effects of blended learning quality and self-directed learning on economic study’s learning outcomes of senior high school in the city of Bogor. The sampling technique in this study used multistage random sampling. The sample used was 282 students. The research method used was an explanatory survey and analyzed using path analysis. The results of this study indicate: (1) There is a positive and significant effect of blended learning quality on economics study’s learning outcomes of senior high school in the city of Bogor. (2) There is a positive and significant effect of self-directed learning on economics study’s learning outcomes of senior high school in the city of Bogor. (3) There is a positive and significant effect of blended learning quality on self-directed learning of senior high school in the city of Bogor. (4) There is a positive and significant effect of blended learning quality on economics study’s learning outcomes through the self-directed learning of senior high school in Bogor city.